Dynamic synthetic-scanning photoacoustic tracking monitors hepatic and renal clearance pathway of exogeneous probes in vivo - Jing Lv; Hengrong Lan; Aoji Qin; Tong Sun; Dan Shao; Fei Gao; Junjie Yao; Kamran Avanaki; Liming Nie (Light: Science & Applications)
Abstract Advancements in precision medicine necessitate understanding drug clearance pathways, especially in organs like the liver and kidneys. Traditional techniques such as PET/CT pose radiation hazards, whereas optical imaging poses challenges in maintaining both depth penetration and high resolution. Moreover, very few longitudinal studies have been performed for drug candidates for different symptoms. Leveraging non-ionizing photoacoustic tomography for deep tissue imaging, we developed a spatiotemporally resolved clearance pathway tracking (SRCPT) method, providing unprecedented insights into drug clearance dynamics within vital organs. SRCPT addresses challenges like laser fluence attenuation, enabling dynamic visualization of drug clearance pathways and essential parameter extraction. We employed a novel frequency component selection based synthetic aperture focusing technique (FCS-SAFT) with respiratory-artifacts-free weighting factors to enhance three-dimensional imaging resolutions. Inspired by this, we investigated the clearance pathway of a clinical drug, mitoxantrone, revealing reduced liver clearance when hepatic function is impaired. Furthermore, immunoglobulin G clearance analysis revealed significant differences among mice with varying renal injury degrees. The accuracy of our method was validated using a double-labeled probe [68Ga]DFO-IRDye800CW, showing a strong positive correlation between SRCPT and PET. We believe that this powerful SRCPT promises precise mapping of drug clearance pathways and enhances diagnosis and treatment of liver and kidney-related diseases.